PENGUATAN KARAKTER RELIGIUS LANSIA MELALUI PENDEKATAN TASAWUF DI PONDOK LANSIA - Khusnul Fathoni; Chanifah, Nur; Siti Rohmah; M. Rohma Rozikin (Wisesa: Jurnal Pengabdian Masyarakat, 2024)
This service activity is intended to provide guidance to the elderly, which has not been done by many educational, social and community institutions. The coaching activities are focused on religious guidance for the elderly. Given that at his age, of course, the need for religious spirituality is a necessity. This service activity was carried out at the Muslim Kaffah elderly cottage in Malang city. These activities include pre-activities, during activities (coaching and socialization, and post-activities in the form of evaluation. The topic raised in the coaching activity was about ikhlas. There are several tips to be able to maintain sincerity, namely (1) Praying to always be sincere in worship, (2) In doing good deeds, seeing people who are better, (3) Feeling afraid that his practice is not accepted by Allah, (4) Not easily influenced by human speech, (5) Believing that no one has power over heaven and hell, (6) Eighth: Always remembering to be alone in the grave. These activities are very beneficial for the elderly, so there needs to be cooperation with the government to develop these activities.